Clusterin/apolipoprotein J binds to aggregated LDL in human plasma and plays a protective role against LDL aggregation. Issue 5 (30th December 2014) - Martínez‐Bujidos, Maria; Rull, Anna; González‐Cura, Beatriz; Pérez‐Cuéllar, Montserrat; Montoliu‐Gaya, Laia; Villegas, Sandra; Ordóñez‐Llanos, Jordi; Sánchez‐Quesada, José Luis
ABSTRACT: Clusterin/apolipoprotein J (apoJ) is an extracellular chaperone involved in the quality control system against protein aggregation. A minor part of apoJ is transported in blood bound to LDLs, but its function is unknown. Our aim was to determine the role of apoJ bound to LDLs. Total LDL from human plasma was fractionated into native LDL [LDL(+)] and electronegative LDL [LDL(‐)]. The latter was separated into nonaggregated [nagLDL(‐)] and aggregated LDL(‐)[agLDL (‐)]. The content of apoJ was 6‐fold higher in LDL(‐) than in LDL(+) and 7‐fold higher in agLDL(‐) than in nagLDL(‐). The proportion of LDL particles containing apoJ (LDL/J+) was 3‐fold lower in LDL(+) than in LDL(‐). LDL/J+ particles shared several characteristics with agLDL(‐), including increased negative charge and aggregation. apoJ‐depleted particles (LDL/J‐) showed increased susceptibility to aggregation, whether spontaneous or induced by proteolysis or lipolysis, as was revealed by turbidimetric analysis, gel filtration chromatography, lipoprotein precipitation, native gradient gel electrophoresis, circular dichroism, and transmission electronic microscopy. The addition of purified apoJ to total LDL also prevented its aggregation induced by proteolysis or lipolysis. These findings point to apoJ as a key modulator of LDL aggregation and reveal a putative new therapeutic strategy against atherosclerosis.—Martínez‐Bujidos, M., Rull, A., González‐Cura, B., Pérez‐Cuéllar, M., Montoliu‐Gaya, L., Villegas, S., Ordóñez‐Llanos, J., Sénchez‐Quesada, J. L. Clusterin/apolipoprotein J binds to aggregated LDL in human plasma and plays a protective role against LDL aggregation. FASEB J. 29, 1688‐1700 (2015). www.fasebj.org